Two new species of the genus Chlopsis (Teleostei: Anguilliformes: Chlopsidae) from the Southwestern Pacific - Tighe, Kenneth A.; Mccosker, John E. (Zootaxa, 2003)
Chlopsis slusserorum, from Fiji and the Solomon Islands, and Chlopsis bidentatus, from Fiji and New Caledonia, two new deepwater species of false moray eels belonging to the family Chlopsidae, are described and illustrated. Chlopsis slusserorum is distinguished from all other chlopsids by its combination of high vertebral count and distinctive pigmentation. Chlopsis bidentatus is distinguished by the combination of bicolored pigmentation, dorsal origin slightly behind gill opening and anteriorly biserial vomerine dentition.